First Nations Women's Evacuation During Pregnancy from Rural and Remote Reserves - Lawford, Karen (Université d'Ottawa / University of Ottawa, 2011)
Pregnant First Nations women who live on reserves in rural and remote regions of Canada are routinely evacuated to urban cities to await labour and birth; this is commonly referred to as Health Canada’s evacuation policy. I produced two stand alone papers to investigate this policy. In the first, I investigated the development and implementation of the Canadian government’s evacuation policy. Archival research showed that the evacuation policy began to take shape in 1892 and was founded on Canada’s goals to assimilate and civilize First Nations. My second paper employed First Nations feminist theory to understand why the evacuation policy does not result in good health, especially for First Nations women. Because the evacuation policy is incongruent with First Nations’ epistemologies, it compromises First Nations’ health. I offer policy recommendations to promote First Nations health in a way that is consistent with First Nations’ epistemologies and goals towards self-determination and self-governance.
Keywords: First Nations; Policy; Health; Evacuation Policy; Archival research